Pemetaan Daerah Rawan Konflik Sosial di Kabupaten Tanggamus - Fahmi, Teuku; Akbar, M. Zaimuddin (JURNAL SOSIOLOGI, 2015)
The study was carried out to obtain the anatomy of conflict and spreading patterns by region in Tanggamus, Lampung province. This study uses a quantitative approach. The data used is data intensity (frequency) for both that are still in the form of conflict or potential conflict that has occurred in Tanggamus in 2014. The results of this study indicate that (1) Tanggamus have a fairly wide area coverage from one region to another. The condition can be an opportunity or obstacle, even can also be a threat to the welfare of society. To that end, the provision of physical and non-physical infrastructure that is easily accessible/used by the public should be of particular concern for the stakesholders in Tanggamus. (2) Regarding to social conflict in Tanggamus, when referring to the data in the previous year (2014), showed that Tanggamus has the potential conflicts that quite alarming when it is not carried out a series of efforts to prevent conflict. The results of the identification of the data shows that there are 22 regions with the potential for conflict in this region. and; (3) There are variations in the background there is the potential for social conflict in Tanggamus, based on the field/category of potential conflict, it appears that at every district has a distinctive pattern. There is one case of potential conflict that comes from social factors, and in other cases the economic factor comes to land/agrarian.Keywords: Mapping, social conflict